Respiratory pathogens in cases of Sudden Unexpected Death in Infancy (SUDI) at Tygerberg forensic pathology service mortuary - La Grange, Heleen (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScMedSc)--Stellenbosch University, 2014.